Where did my energy go? The effects of interference on the output of vibrator fleets - Dean, Timothy; Tulett, J.; Lane, D. (2015)
© 2015 SEG.Multiple hydraulic vibrators are often used together as the source for seismic surveys to increase the amount of energy transmitted, but it has been observed that the increase is less than theoretically predicted. By measuring the acceleration of the reaction-mass and baseplate on a vibrator that was not sweeping, but that was placed close to one that was, we show that this loss of energy is likely due to interference between the vibrators ground-force measurements reducing the output of the vibrators.